Detection sensitivity correction calculation model and application of photoelectric detection target in four-screen intersection testing system. (June 2021) - Li, Hanshan; Zhang, Xiaoqian; Zhang, Xuewei; Lu, Liping
Highlights: Propose array photoelectric detection receiver to design a new photoelectric detection target. Propose a new calculation detection sensitivity method of the photoelectric detection target. Present a detection sensitivity correction model of four-screen intersection testing system. Abstract: In four-screen intersection testing system, the inconsistency in the detection sensitivity of the photoelectric detection target leads to the errors in the time value extraction for each photoelectric detection target. To improve the detection sensitivity and the measurement accuracy, we propose the array photoelectric detection receiver to design a new photoelectric detection target, set up a new method for calculating the detection sensitivity of the photoelectric detection target based on the detection field of view, detection screen thickness, detection distance, and the target's geometry, and present a detection sensitivity correction method for four-screen intersection testing system by introducing the sensitivity correction factor. Through the comparative experiments, we present the comparative test data when the projectile passes through different positions of the field of view of photoelectric detection target for different detection distances. The results show that the proposed detection sensitivity correction model has the ability to improve the measurement accuracy.